Pengaruh Struktur Aset dan Profitabilitas Terhadap Leverage Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018 - Sarli Mardiana; Elvi Rahmi (Jurnal Salingka Nagari, 2023)
This study objectives to determine the effect of asset structure and profitability on leverage in mining companies listed on the IDX in 2014-2018, the effect of asset structure on the leverage of mining companies listed on the IDX in 2014-2018, the effect of profitability on the leverage of mining companies listed on the IDX in 2014-2018. This research is classified as a causative research with a population of 42 mining companies listed on the IDX in 2014-2018 and sample 16 companies. The type of data used is secondary data, namely the financial statements of mining companies sourced from the official IDX website, namely www.idx.co.id and ICMD using the documentation method. The analysis used is the classical assumption test, multiple linear regression, the coefficient of determination (R2), the F test and the t test using the SPSS v.22 program. The test results show that the asset structure and profitability have a significant effect on the leverage of mining companies listed on the IDX in 2014-2018. The asset structure has a positive and significant effect on the leverage of mining companies listed on the IDX in 2014-2018. Profitability has a negative and significant effect on the leverage of mining companies listed on the IDX in 2014-2018